2004
DOI: 10.1167/iovs.03-1370
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Splice Mutation in theHSF4Gene Is Associated with an Autosomal Recessive Congenital Cataract

Abstract: This is the first report describing association of an autosomal recessive cataract with the HSF4 locus on 16q21-q22.1 and the first description of HSF4 splice variants in the lens showing that HSF4b is the major transcript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 21 publications
1
65
0
Order By: Relevance
“…Mutations in HSF4 have been associated with both autosomal dominant and recessive cataracts. The dominant cataracts present in early childhood and are described as lamellar [70], including the historically important Marner family cataract [71], whereas, the recessive cataracts had a congenital onset and ranged in severity from nuclear with some cortical involvement [72] to total lens opacities at birth with associated nystagmus [73]. Interestingly, the dominant mutations in HSF4 lie within the α-helical DNA-binding domain, whereas, the recessive mutations lie outside this highly conserved functional domain.…”
Section: Growth and Transcription Factorsmentioning
confidence: 99%
“…Mutations in HSF4 have been associated with both autosomal dominant and recessive cataracts. The dominant cataracts present in early childhood and are described as lamellar [70], including the historically important Marner family cataract [71], whereas, the recessive cataracts had a congenital onset and ranged in severity from nuclear with some cortical involvement [72] to total lens opacities at birth with associated nystagmus [73]. Interestingly, the dominant mutations in HSF4 lie within the α-helical DNA-binding domain, whereas, the recessive mutations lie outside this highly conserved functional domain.…”
Section: Growth and Transcription Factorsmentioning
confidence: 99%
“…In humans, mutations in HSF4 are associated with various recessive and dominant forms of congenital and age-related cataracts [109][110][111][112][113][114][115]. Similarly, the Hsf4 knockout mice (Hsf4 2/2 ) develop cataracts.…”
Section: Genes Causing Juvenile Cataractmentioning
confidence: 99%
“…This is consistent with other studies that have identified an important role for mammalian HSF4 in lens development and differentiation of lens fibers. Mutations in HSF4 genes have been linked to several human families with hereditary congenital cataracts as well as several dog breeds that also frequently exhibit juvenile cataracts (Bu et al 2002;Smaoui et al 2004;Ke et al 2006;Mellersh et al 2006;Engelhardt et al 2007). Several of these mutations occur in the DNA binding domain of the protein and affect the ability of HSF4 to bind to HSE sequences .…”
Section: Discussionmentioning
confidence: 99%
“…The reduced severity of the small eye phenotype in the hsf1 knockdowns suggested that there are likely other factors involved in regulating hsp70 expression in the zebrafish lens. Both HSF1 and HSF4 play a role in mammalian lens development (Fujimoto et al 2004;Min et al 2004;Smaoui et al 2004;Mellersh et al 2006;Fujimoto et al 2008;Shi et al 2009;Abane and Mezger 2010), suggesting that the zebrafish hsf4 recently identified in an expressed sequence tag (EST) library could play a similar role. Here, we have carried out a comparative sequence analysis of zebrafish HSF4 to zebrafish HSF1 and HSF2, as well as HSFs from a wide range of organisms.…”
Section: Introductionmentioning
confidence: 99%